x^2 +x-2019 *2020 = 0
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
thêm \(\dfrac{1}{2021}+\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2}\ne0\) nên nó z nha :Đ giải thích ấy
`<=>(x+1)/2021+1+(x+2)/2020+1+(x+3)/2019+1+(x+2028)/2-3=0`
`<=>(x+2022)/2021+(x+2022)/2020+(x+2022)/2019+(x+2022)/2=0`
`<=>(x+2022)(1/2021+1/2020+1/2019+1/2)=0`
`<=>x+2022=0`
`<=>x=-2022`
\(\dfrac{x+1}{2020}+\dfrac{x+2}{2019}+\dfrac{x+3}{2018}+\dfrac{x+4}{2017}+4=0\)
⇔ \(\dfrac{x+1}{2020}+1+\dfrac{x+2}{2019}+1+\dfrac{x+3}{2018}+1+\dfrac{x+4}{2017}+1=0\)
\(\Leftrightarrow\) \(\dfrac{x+2021}{2020}+\dfrac{x+2021}{2019}+\dfrac{x+2021}{2018}+\dfrac{x+2021}{2017}=0\)
⇔ \(\left(x+2021\right)\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)=0\)
\(Do\) \(\left(\dfrac{1}{2020}+\dfrac{1}{2019}+\dfrac{1}{2018}+\dfrac{1}{2017}\right)\ne0\)
⇒ \(x+2021=0\)
⇔ \(x=-2021\)
\(Vậy\) \(x=-2021\)
=>\(\left(\dfrac{x+1}{2021}+1\right)+\left(\dfrac{x+2}{2020}+1\right)+\left(\dfrac{x+3}{2019}+1\right)+\left(\dfrac{x+2028}{2}-3\right)=0\)
=>x+2022=0
=>x=-2022
(x-2020)x - 1 - (x - 2020)x + 2019 = 0
=> (x - 2020)x - 1 .[(x - 2020)2020 - 1] = 0
=> \(\orbr{\begin{cases}\left(x-2020\right)^{x-1}=0\\\left(x-2020\right)^{2020}-1=0\end{cases}\Rightarrow\orbr{\begin{cases}x-2020=0\\\left(x-2020\right)^{2020}=1^{2020}\end{cases}\Rightarrow}\orbr{\begin{cases}x-2020=0\\x-2020=\pm1\end{cases}}}\)
=> \(x-2020\in\left\{0;1;-1\right\}\Rightarrow x\in\left\{2020;2021;2019\right\}\)
\(x^2+x-2019\cdot2020=0\)
\(\Leftrightarrow\left(x+2020\right)\left(x-2019\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-2020\\x=2019\end{matrix}\right.\)